2012
DOI: 10.1111/j.1463-5224.2012.01008.x
|View full text |Cite
|
Sign up to set email alerts
|

Outbreak of Philophthalmus gralli in four greater rheas (Rhea americana)

Abstract: Using slit‐lamp biomicroscopy, conjunctival biopsy, and morphological identification, a flock of four Greater rheas (Rhea americana) in Arizona were diagnosed with conjunctivitis secondary to Philophthalmus gralli (P. gralli) infection. Aquatic snails from the exhibit’s water source were identified as Melanoides tuberculatus, a known vector for P. gralli. Comparison of partial sequences of DNA regions from P. gralli adults removed from the rheas and metacercariae from the aquatic snails demonstrated a 100% mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 41 publications
2
22
0
1
Order By: Relevance
“…The morphological characteristic of P. gralli was confirmed under an optical microscope. Moreover, the conjunctival trematode from the ostrich in the present study was identified as P. gralli , which was submitted to GenBank database under accession numbers MZ088139, 99.92% identity to P. gralli isolate from Greater rheas (Rhea Americana) in Arizona (JQ246434) [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The morphological characteristic of P. gralli was confirmed under an optical microscope. Moreover, the conjunctival trematode from the ostrich in the present study was identified as P. gralli , which was submitted to GenBank database under accession numbers MZ088139, 99.92% identity to P. gralli isolate from Greater rheas (Rhea Americana) in Arizona (JQ246434) [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the phenotypic and the genotypic characteristics of P. gralli were confirmed by using the optical microscope and the direct sequencing of PCR product, respectively. The parasite sequences were found in GenBank, with accession numbers from Greater rheas ( Rhea Americana ) in Arizona [ 20 ]. These processes ensured the accuracy of P. gralli identity that was used in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although native to Asia and Africa, the snail has been introduced around the world, including in the Americas from the United States to southern Brazil (Murray 1971, Facon et al 2003, Coelho et al 2018, CABI 2020, Chalkowski et al 2021). At least three human-pathogenic, zoonotic trematodes have been co-introduced with the snail in the Americas (see Scholz et al 2001, Pinto & Melo 2011 and refs therein), including reports in the continental United States of all three species in Texas (Nollen & Murray 1978, Mitchell et al 2000, Tolley-Jordan & Owen 2008), one in Arizona (Church et al 2013), and another in Utah and Florida (Mitchell et al 2005). However, M. tuberculata is much more widespread throughout the Unites States (Chalkowski et al 2021) than the few places the trematodes have been reported.…”
Section: Textmentioning
confidence: 99%
“…en Cryptosporidium spp. en myiasis (Abrams et al, 2002;Dubey, 2002;Elias et al, 2008;Lopez et al, 2010;Church et al, 2013;Dunham et al, 2016). Veel van deze parasieten komen echter zelden voor in West-Europa en infecties worden vaak uitsluitend waargenomen bij in het wild levende dieren of in het wild gevangen dieren.…”
Section: Inleidingunclassified